Introducing a new triazoloquinoxaline-based fluorene copolymer for organic photovoltaics: Synthesis, characterization, and photovoltaic properties - Baran, Derya; Pasker, Felix M.; Le Blanc, Stephan; Schnakenburg, Gregor; Ameri, Tayebeh; Hoeger, Sigurd; Brabec, Christoph (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
A new donor-acceptor copolymer consisting of triazoloquinoxaline and 9,9-dialkylfluorene units on the main chain has been synthesized, characterized and evaluated as donor material in bulk heterojunction solar cells using PC BM as an acceptor. The resulting polymer PTQF showed good thermal stability and solubility in common organic solvents. Cyclic Voltammetry measurements showed that the PTQF has HOMO-LUMO energy levels of -5.13 and -3.62 eV, respectively. DFT calculations revealed that the HOMO is delocalized all over the thiophene and fluorene units and the LUMO is localized mainly on the triazole and pyrazine units. PTQF absorbs broadly in the visible region and exhibits a bandgap of 1.4 eV. Photovoltaic devices exhibited 1.7% efficiency for 1:2 PTQF:PCBM blend ratio using Ca/Ag electrodes. © 2012 Wiley Periodicals, Inc.
Keywords: benzotriazole; conducting polymers; conjugated polymers; electrochemistry; fluorene copolymer; organic photovoltaics; Suzuki coupling; triazoloquinoxaline